Efeito repetido do uso das redes sociais em smartphones imediatamente antes das sessões de treinamento sobre a eficácia técnica, desempenho percepto-cognitivo e físico em jovens atletas de voleibol - Freitas Junior, Carlos Gilberto de (2023)
Mental fatigue (MF) is a psychobiological state resulting from participation in cognitively demanding activities, characterized by a feeling of tiredness, lack of energy, alteration in the neuroelectric activity of the brain, and aversion to continuing the task performed. According to the scientific literature, MF can be caused by using social media on smartphones, causing damage to sports performance, more precisely to technical, physical, and perceptual-cognitive performance. However, the studies carried out, for the most part, observed the effects of the use of social media on sports performance in an acute way, and the specialized literature lacks more findings on the damage caused in the long term, also known as the repeated effect. Thus, this thesis aimed to verify the repeated effect of using social media on smartphones immediately before training sessions on technical efficacy, and physical, and perceptual-cognitive performance in young volleyball athletes. A study of repeated measures with crossover design was carried out, lasting six weeks, with the participation of 14 male volleyball athletes, under 19, selected in a non-probabilistic way (age, 17,57 ± 0,65 anos; body mass, 76,97 ± 15,35 kg; eight, 187,57 ± 7,42 cm). The athletes participated in their training routines for six weeks under different conditions, three weeks using social media on smartphones (SMA) and three weeks watching documentaries about the Olympics (DOC) for 30 minutes before the training sessions. MF was evaluated daily before and after the experimental protocols (using social media or watching documentaries) using the visual analog scale (VAS). Before and after the experimental conditions, the athletes were submitted to tests of decision-making (DM) in perspectives of first (DM1ª) and third (DM3ª) people, multiple objects tracking ability(MOT), the effectiveness of attack (EA) and repeat jumping ability (RJA). The internal training load (ITL) for the three weeks was analyzed using the session rating of perceived exertion method (s-RPE). The averages of VAS sessions (pre vs. post-experimental conditions) for the three weeks were used for analysis. A two-way ANOVA of measures was used to analyze the main effect of interaction condition (SMA vs. DOC) vs. time (pre vs. post-experiment) for VAS, DM1ª, DM3ª, RMO, EA, and RJA. Both conditions showed an increase in VAS after three weeks (p < 0.001; ηp2 = 0.84), with SMA showing a greater increase compared to DOC (p < 0.05). Only DOC improved the response time for the DM1ª (p = 0.03; ηp2 = 0.18). For DM3ª, DOC improved accuracy (p = 0.63; ηp2 < 0.01) and response time (p = 0.63; ηp2 < 0.01) compared to SMA. After three weeks, only DOC EA was improved (p < 0.01; ηp2 = 0.28). No differences were found for MOT and RJA. It is concluded that the repeated use of social networks on smartphones before training sessions for three weeks generates MF and compromises the development of DM and EA in young volleyball athletes.